Digital Linguistics in Human Resource Management: Code-Switching, Emojis, and Hashtags in Employee Engagement - Safii, Muhammad; Puspita, Clara; Br. Perangin -Angin, Sempa (Journal of English Language and Education, 2025)
This study examines the role of digital linguistics—emoji use, code-switching, and hashtags—in shaping employee engagement within a private logistics company in Medan, Indonesia. Using a qualitative case study approach, data were collected through semi-structured interviews with employees actively engaged in internal digital communication, and were analyzed thematically. Findings indicate that emojis help soften messages, reduce tension, and foster warmth in workplace interactions. Code-switching between Indonesian, English, and local dialects functions as a social adaptation strategy and professional identity marker. Hashtags, though less frequent, act as symbolic tools for uniting teams, reinforcing collective identity, and emphasizing project goals. Together, these practices enrich digital communication and support the dimensions of vigor, dedication, and absorption in employee engagement. Grounded in Social Exchange Theory (SET) and Media Richness Theory (MRT), this research underscores digital linguistics as a strategic HRM tool for enhancing engagement, while highlighting organizational reputation and governance as crucial supporting factors.